From George H. W. Bush to Donald Trump. Presidents’ pledges on trade and what they accomplished (1989-2021) - Contrera, Flávio; Pasquariello Mariano, Karina Lilia; Goulart Menezes, Roberto (Estudios Internacionales, 2024)
This article evaluates the fulfillment of electoral pledges on trade policy by US presidents in the period from 1989 to 2021 with the aim of identifying patterns of continuity and change in the agenda of the parties and the country. The identification of promises was made based on the analysis of the campaign manifestos of the parties of the presidents elected in the period. The criterion established to evaluate the fulfillment of the pledges was the implementation of an action. There are similar degrees of compliance between Democrats and Republicans, whose agendas (i) are similar in terms of free trade agreements and protectionist measures and (ii) diverge in relation to the adherence of labor rights and environmental protection commitments in these agreements. Original, it contributes to the debate on the quality of democratic representation by measuring the degree of responsiveness of political parties in a policy of special interest to American workers. At the same time, it shows how bipartisan continuity and convergence were fundamental in guiding US trade policy.